Autopia Dunia Kerja: Studi Eksploratory Praktik Diskriminasi di Tempat Kerja - Widyadmono Mardi; Yudi Yuniarto (Universitas Sahid Surakarta, 2024)
In Indonesia's pluralistic society, is the hope of equal employment opportunities a dream (autopia)? This research explores the experience of worker discrimination, the basis of discriminatory treatment and responses to discriminatory treatment. Researchers interviewed workers with an accidental sampling approach. Interviews were conducted on 206 workers working in Java and outside Java. Research findings showed that 82.52% of the sample reported not experiencing discrimination at work, and the remaining 17.48% reported discriminatory treatment at work. Realizing the expectation of working without discrimination is not autopia. The perceived discriminatory treatment grounds were seniority (30%), religion, race, gender (17% each), structural and physical (8%) and regional origin (2.78%). While the response to discriminatory treatment shown was silence (39%), report superiors (30%) and confrontation (19%). Using binary logistic regression analysis, discriminatory treatment was positively influenced significantly by gender, length of service, and location. Advocacy for equal rights needs to be done.